A nomogram of suicidal ideation among men who have sex with men in China: Based on the integrated motivational-volitional model of suicidal behavior - Xu, Chen; Wang, Zuxin; Liu, Shangbin; Chen, Hui; Chen, Yingjie; Xia, Danni; Chen, Yufei; Xu, Huifang; Hu, Fan; Wang, Ying; Cai, Yong; Chen, Jianyu (Frontiers in Public Health, 2022)
Introduction Men who have sex with men (MSM) are a high-risk group for suicide, with a much higher prevalence of suicidal ideation (SI) than the general population and male population. The aim of this study was to explore the risk factors influencing the development of SI and to develop and validate a nomogram among MSM. Methods A cross-sectional study was conducted in 915 MSM from Shanghai, Shenyang, Shenzhen and Kunming, China using the snowball sampling method. The integrated motivational-volitional (IMV) model of suicidal behavior was used as a theoretical framework to collect different potential influencing factors of SI including diathesis-environment-life events factors and psychosocial factors. The risk factors of SI were screened by logistic regression analysis, and a nomogram for predicting SI were developed. Model properties including discrimination, calibration and decision curves were evaluated to validate the prediction model. Results 882 MSM were included in the statistical analysis, with a lifetime prevalence of SI of 34.4% (303/882). Logistic regression analysis showed that age group, sexual orientation disclosure, high-risk sexual behavior, entrapment, defeat and interpersonal needs were associated with SI. A nomogram was constructed based on the above six predictors. AUC values of ROC for prediction model were 0.761 (0.641–0.770) and 0.754 (0.565–0.822) in the training set (n = 662) and validation set (n = 220), respectively. And there was no statistical difference of the AUC values between the two sets (P > 0.05). The calibration plots of the prediction model in both sets fit well with the ideal model (P > 0.05). The decision curves demonstrated that the threshold probability of prediction model in training set was 1–85%, whereas in validation set was 1–63%. Conclusions The lifetime prevalence of SI among Chinese MSM is high. The nomogram can serve as a useful tool to predict the development of SI among MSM. Defeat, entrapment and interpersonal needs, as significant predictors of SI, can be measured to identify SI in advance. Early assessment of SI and the enhancement of psychosocial interventions are important to prevent suicide-related behaviors. Future studies could incorporate more variables of interest to refine the prediction model to better guide behavioral and psychological intervention strategies among MSM.